Exploring EFL Teachers’ Beliefs on the Implementation of Learner Autonomy in Online Classrooms: Learner Autonomy, Teachers’ Beliefs, Online Classrooms, Technology - Yayu Nopriani Martha; Gin Gin Gustine; Ahmad Bukhori Muslim (Universitas Islam Negeri (UIN) Mataram, 2021)
Learner Autonomy is a dynamic process in which learners take an active role and are responsible for their learning. Nowadays, teachers and learners are using technology in online classrooms due to the pandemic situation during which learner autonomy can play critical roles. However, studies investigating teachers’ beliefs in fostering learner autonomy by utilizing technology in online classrooms remain sparse. To fill this gap, this qualitative study explored the teachers' beliefs in fostering learner autonomy by using technology in online classrooms. Drawing on the data garnered from online questionnaires and open-ended questions that involved 48 English teachers from various levels of education in Central Kalimantan with different teaching experience and education degrees, it was found that the teachers deployed various technological tools, which helped them foster learner autonomy in online classrooms.